Does international experience form a sustainable competitive advantage at the executive level? - Egunlae, Vincent (2017)
International experience is a scarce, but desired resource at the top level of management. Multinationals with internationally experienced CEO’s tend to innovate more and perform better than multinationals without them, forming a competitive advantage. It is not known how the passage of time will affect the sustainability of this source of competitive advantage. This paper uses insights from the diffusion of innovations theory, to gain an understanding of how temporal growth in the number of internationally experienced managers may vitiate the strength of its competitive advantage. Using the English Premier League (1995 – 2017) as a case study to better understand this possibility in context, it is strongly suggested whilst international experience may form a competitive advantage for an organization, it is likely to prove increasingly temporary as time passes. The diffusion of innovations theory provides a rubric to understand the factors that can affect the acceleration or deceleration of this process in a context that can be generalized.